2003
DOI: 10.1021/tx034037j
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Hydroxybenzoate Saxitoxin Analogues Isolated from the Dinoflagellate Gymnodinium catenatum

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 7 publications
2
90
0
1
Order By: Relevance
“…Sub-fractionation in the initial preparative chromatography yielded putative GC3 toxin (m/z 377>257) in sub-fraction F3.3. Refractionation was successful in obtaining this GC3 toxin with higher purity, but given that the GC3 structure has been previously confirmed by 1 H-NMR [16] this component was not subjected to further confirmation in our study. The two low abundant peaks at transition m/z 393>273 are consistent with the molecular masses of GC6 and GC3a.…”
Section: Fraction 3 (100% Meoh)mentioning
confidence: 80%
See 2 more Smart Citations
“…Sub-fractionation in the initial preparative chromatography yielded putative GC3 toxin (m/z 377>257) in sub-fraction F3.3. Refractionation was successful in obtaining this GC3 toxin with higher purity, but given that the GC3 structure has been previously confirmed by 1 H-NMR [16] this component was not subjected to further confirmation in our study. The two low abundant peaks at transition m/z 393>273 are consistent with the molecular masses of GC6 and GC3a.…”
Section: Fraction 3 (100% Meoh)mentioning
confidence: 80%
“…Further investigations revealed that these compounds, named GC1-3 toxins, were indeed new analogs. Extracts containing these analogs were purified for the first time by hydrophilic interaction liquid ion-chromatography (HILIC), and their structures were characterized by mass spectrometry (MS) and nuclear magnetic resonance (NMR) [16]. According to these authors, the GC3 analog is the para-hydroxybenzoyl derivative of dcSTX; GC1 and GC2 are C-11 sulfated variants of GC3 that form an enantiomeric pair depending on the stereochemical position of the sulfate group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uppermost molecule is saxitoxin itself with the two analogues shown below having had their carbamoyl chain modified. The leftmost analogue is a hydroxybenzoate saxitoxin (Negri et al 2003) while the carbamoyl chain has been completely removed in the right-hand analogue, decarbamoylSTX (Koehn et al 1981). In all cases, the 1,2,3 guanidinium group is pointing upwards and the elements are colored as in Fig.…”
Section: Analogues Of Saxitoxin and Tetrodotoxinmentioning
confidence: 99%
“…The discovery of new STX analogues has accelerated recently partly due to the realization that standard analytical techniques and sample preparation eliminated them from many extracts (Negri et al 2003(Negri et al , 2007. These toxins are potent Na channel binding toxins (Llewellyn et al 2004).…”
Section: Future Directionsmentioning
confidence: 99%